" CAPTUREWEDDING " ADOLESCENT BEHAVIOR CONTROL IN THE AIR BANGIS NAGARI WEST PASAMAN - Fitri, DediMardia; Erianjoni, Erianjoni; Elvawati, Elvawati (Pendidikan Sosiologi, 2014)
This study aimed to describe social control through mating arrested in Nagari Air Bangis               WestPasaman.The approach used is descriptive qualitative approach. Determination of purposive informant done. Data was collected through observation, interviews, and documentation. The unit of analysis is the individual, kewilayah and time according to the research focus. Data analysis method used is descriptive analysis of the data was analyzed according to the interactive model (Interactive Model OfAnalysis) Miles &Hubermas.The results showed that the mating behavior of control teens arrested in Nagari Air Bangis generally concluded that the mating catch is a sanction given by the villagers Air Bangis against teens who violate the ordinance association, in which the mating process which begins with the arrest here of surveillance , in where the teen initially staked out by youths around , then the arrest is an act of investigating a temporary restraint, then calling parents, teens who are arrested can not be processed without the presence of their parents, the next to marry is a process of settlement of the juveniles arrested for have violated procedures in Nagari Air Bangisassociation .